Toll-Interleukin 1 Receptor Domain-Containing Adaptor Protein 180L Single-Nucleotide Polymorphism Is Associated With Susceptibility to Recurrent Pneumococcal Lower Respiratory Tract Infections in Children - Siebert, Johan N.; Hamann, Lutz; Verolet, Charlotte M.; Gameiro, Cécile; Grillet, Stéphane; Siegrist, Claire-Anne; Posfay-Barbe, Klara M. (Frontiers in Immunology, 2018)
Lower respiratory tract infections (LRTI) are often caused by Streptococcus pneumoniae (Spn) and can be recurrent in 8% of children older than two years of age. Spn is recognized by pattern-recognition receptors (PRRs) of the innate immune system, in particular Toll-like receptors (TLRs) 2 and 4. To assess whether a defect somewhere along this TLR signaling pathway increases susceptibility to recurrent pneumococcal LRTI, we conducted a prospective case-control study with 88 healthy individuals and 45 children with recurrent LRTI aged 2 to 5 years old. We examined cell surface expression of TLR2 and TLR4, as well as 8 genetic variants of these receptors or associated co-receptors TLR1 and TLR6. IL-6 production was measured after whole blood stimulation assays with specific agonists and heat-killed Spn. Our findings reveal that single nucleotide polymorphisms within toll-interleukin 1 receptor domain-containing adaptor protein (TIRAP) alone or in combination with TLR1 N248S, TLR1 I602S or TLR6 S249P polymorphisms contributes to various degree of susceptibility to recurrent pneumococcal lower respiratory tract infections in children by modulating the inflammatory response. In that respect, carriage of the TIRAP S180L heterozygous trait increases the likelihood to protect against pneumococcal LRTI, whereas children carrying the mutant homozygous TIRAP 180L polymorphism might be more likely susceptible to recurrent pneumococcal LRTI.